Science with the Murchison Widefield Array - Arcus, Wayne; Emrich, David; Herne, David; Lynch, Mervyn; Ord, Stephen; Tingay, Steven; Wayth, Randall; Waterson, Mark; Bowman, Judd; Cairns, Iver; Kaplan, David; Murphy, Tara; et al. (CSIRO, 2013)
Significant new opportunities for astrophysics and cosmology have been identified at low radio frequencies. The Murchison Widefield Array is the first telescope in the southern hemisphere designed specifically to explore the low-frequency astronomical sky between 80 and 300 MHz with arcminute angular resolution and high survey efficiency. The telescope will enable new advances along four key science themes, including searching for redshifted 21-cm emission from the EoR in the early Universe; Galactic and extragalactic all-sky southern hemisphere surveys; time-domain astrophysics; and solar, heliospheric, and ionospheric science and space weather. The Murchison Widefield Array is located in Western Australia at the site of the planned Square Kilometre Array (SKA) low-band telescope and is the only low-frequency SKA precursor facility. In this paper, we review the performance properties of the Murchison Widefield Array and describe its primary scientific objectives.